2022
DOI: 10.3389/fonc.2022.947332
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autophagy by non-coding RNAs in gastric cancer

Abstract: Autophagy is a conserved cellular self-digesting process that degrades obsoleting proteins and cellular components and plays a crucial role in the tumorigenesis, metastasis, and drug resistance of various tumors such as gastric cancer (GC). As a hotspot in molecular biology, non-coding RNAs (ncRNAs) are involved in the regulation of multiple biological processes, such as autophagy. Increasing evidence indicate that various ncRNAs exert double roles in the initiation and progression of GC, either serve as oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 130 publications
(139 reference statements)
0
0
0
Order By: Relevance
“…The role of ncRNAs in tumorigenesis and immune response has been investigated widely in cancers. In these settings, ncRNAs regulate proliferation, differentiation, apoptosis, necrosis, autophagy, immune response, and inflammation [35,69,83,84]. In colorectal cancer, it was reported that the tumor suppressor miR-195-5p promotes TAM polarization by suppressing NOTCH2 expression [85].…”
Section: Ncrnas and Immune Responsementioning
confidence: 99%
“…The role of ncRNAs in tumorigenesis and immune response has been investigated widely in cancers. In these settings, ncRNAs regulate proliferation, differentiation, apoptosis, necrosis, autophagy, immune response, and inflammation [35,69,83,84]. In colorectal cancer, it was reported that the tumor suppressor miR-195-5p promotes TAM polarization by suppressing NOTCH2 expression [85].…”
Section: Ncrnas and Immune Responsementioning
confidence: 99%
“…The role of ncRNAs in tumorigenesis has been investigated in a wide array of cancers. In this setting, ncRNAs regulate proliferation, differentiation, apoptosis, necrosis, autophagy, immune response, and inflammation (17,(27)(28)(29). In colorectal cancer, it was reported that tumor suppressor miR-195-5p promotes TAM polarization by the suppression of NOTCH2 expression (30).…”
Section: Overview Of Tumor Immunitymentioning
confidence: 99%